Análise da variabilidade das chuvas e sua relação com a produtividade da soja na vertente paranaense da bacia do Paranapanema - Carmello, Vinicius [UNESP] (2013)
Although studies show a gradual decrease in the agriculture dependence on atmospheric weather fluctuations, primarily through the use and integration of the technique in the field (the use and integration of fieldwork), there is much to consider when dealing with the relationship between rainfall and agricultural productivity. With soybean production these proportions rise when considering the flagship of grain exports in the State of Paraná - Brazil. This study's aim was to analyze the rainfall variability and soybean production in the years between 1999/00 to 2009/10 on the southern slope of Paranapanema river basin, observing the soybean yield variations as a result of fluctuations in precipitation patterns. We used rainfall data derived from 89 rain gauge stations along the ANA - Agência Àguas Paraná, these were quantified measurements of annual precipitation and grouped according to the technique percentile among data showing extremely dry periods, dry, normal, rainy and extremely rainy. We analyzed the soybean yield interannual variability, considering 132 municipalities in 11 agricultural seasons. This data was collected from agricultural SEAB - Secretaria Estadual de Abastecimento. This data was processed with the use of conventional statistical software and statistical techniques and the results were presented on maps and graphs favorable to a better understanding and analysis. Some results were significant with regard to the relation of annual rainfall accumulated - reason productivity...